If deficits are not the culprit, what determines Indian interest rates? An evaluation using the maximum entropy bootstrap method - Hrishikesh Vinod; Lekha S. Chakraborty; Honey Karun (Levy Economics Institute of Bard College, 2014)
This paper challenges two clichés that have dominated the macroeconometric debates in India. One relates to the neoclassical view that deficits are detrimental to growth, as they increase the rate of interest, and in turn displace the interest-rate-sensitive components of private investment. The second relates to the assumption of "stationarity" - which has dominated the statistical inference in time-series econometrics for a long time - as well as the emphasis on unit root-type testing, which involves detrending, or differencing, of the series to achieve stationarity in time-series econometric models. The paper examines the determinants of rates of interest in India for the periods 1980-81 and 2011-12, using the maximum entropy bootstrap (Meboot) methodology proposed in Vinod 1985 and 2004 (and developed extensively in Vinod 2006, Vinod and Lopez-de-Lacalle 2009, and Vinod 2010 and 2013). The practical appeal of Meboot is that it does not necessitate all pretests, such as structural change and unit root-type testing, which involve detrending the series to achieve stationarity, which in turn is problematic for evolutionary short time series. It also solves problems related to situations where stationarity assumptions are difficult to verify - for instance, in mixtures of I(0) and nonstationary I(d) series, where the order of integration can be different for different series. [...]
Keywords: E63; H62; 330; Bootstrapping; Fiscal Deficit; Interest Rates; Maximum Entropy; Term Structure